Does technology-based interventions in psychosis improved functioning and quality of life? A systematic review and meta-analysis. (1st June 2022) - Morales-Pillado, C.; Sanchez-Gutierrez, T.; Fernandez-Castilla, B.; Barbeito, S.; Gonzalez-Fraile, E.; Calvo, A.
Abstract : Introduction: Technology-based interventions (TBIs), including computer and Internet-based interventions, mobile interventions, health applications, social media interventions, and interventions using technological devices, could become a useful, effective, accessible, and cost-effective approach (Berry et al., 2016; Firth, 2016) to complement conventional interventions for psychosis Objectives: to compare TBIs with conventional interventions for psychosis, focusing mainly on functioning and quality of life. Methods: The systematic review preceding this work was based on 58 RCT of TBIs for psychosis. We selected the studies that analyzed functioning (N = 23) and quality of life (N = 15). We calculated the standardized mean change (SMC) and applied a three-level model because there were several effect sizes within the same study. Results: There were significant differences between TBIs and conventional interventions for functioning (d = 0.25, SE = 0.09, z = 2.72, p = <.01), but not for quality of life (d = 0.14, SE = 0.08, z = 1.78, p = .076) in patients with psychosis. Conclusions: On average, patients who received TBIs performed better in functioning, but not in quality of life. Functioning is impaired in patients with psychosis, so TBIs should be considered a complement and efficacious intervention, highlighting the power of these type of interventions in improving some outcomes. Disclosure: No significant relationships.